2021
DOI: 10.3389/fvets.2021.646437
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Pimobendan on Cardiac Function in Dogs With Tachycardia Induced Dilated Cardiomyopathy: A Randomized, Placebo-Controlled, Crossover Study

Abstract: Background: Pimobendan provides a significant survival benefit in dogs with cardiac disease, including degenerative mitral valve disease and dilated cardiomyopathy (DCM). Its positive inotropic effect is well-known, however, it has complex effects and the mechanisms behind the survival benefit are not fully characterized. Secondary hemodynamic effects may decrease mitral regurgitation (MR) in DCM, and the benefits of pimobendan may extend to improved cardiac relaxation and improved atrial function.Hypothesis/O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(43 reference statements)
1
0
0
Order By: Relevance
“…In HF, the mitochondria are dysfunctional resulting in impaired myocardial energetics (e.g., decreased ATP content) subsequently less ATP available for muscular relaxation [ 15 ]. Several studies in dogs [ 16 18 ] have shown improvement of diastolic function by pimobendan which could be partly explained by our findings.…”
Section: Discussionsupporting
confidence: 71%
“…In HF, the mitochondria are dysfunctional resulting in impaired myocardial energetics (e.g., decreased ATP content) subsequently less ATP available for muscular relaxation [ 15 ]. Several studies in dogs [ 16 18 ] have shown improvement of diastolic function by pimobendan which could be partly explained by our findings.…”
Section: Discussionsupporting
confidence: 71%